The Bright Side of Social Media: Social Media Platforms Adoption and Start-Up Sustainability - Mujahid, Muhammad Saeed; Mubarik, Muhammad Shujaat (Frontiers in Psychology, 2021)
This paper aims to explicate the contribution of social media platforms adoption on start-up sustainability. Since most economies of the world start-up failure rate are relatively high, there is always a desire or a need to investigate the success recipe. As a result, this study's primary objective is to understand the social media environment and how start-ups can best utilize social media platforms throughout their lifecycle. Based on the qualitative case study approach, four in-depth interviews of social media marketers and individuals working in start-ups were conducted. Finding demonstrates that social media is a crucial virtual platform for striving resource start-ups. Therefore, if the platform gets utilized correctly, it can play an essential role in a start-up's sustainable progression. Thus, there is a need that start-ups should articulate a comprehensive social media policy for each lifecycle stage.